Post a New Question

math

posted by .

Equivalent Expressions
1. Which algebraic expression is equivalent to the expression below?

3(x - 2) + 12(x + 8)

  • math -

    What are your choices?

  • math -

    3(x-2)+12(x+8)=
    3*x-3*2+12*x+12*8=
    3x-6+12x+96=
    15x+90

    3(x-2)+12(x+8)=15x+90

  • math -

    7(4x + 2y), which of these is an equivalent expression?

  • math -

    What are those

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question